THE ROLE OF NITRIC OXIDE IN THE PATHOGENESIS OF TRAUMATIC CRANIAL INJURY ASSOCIATED WITH DIABETES - Meretskyy, V.M. (World of Medicine and Biology, 2013)
The purpose of the study was to investigate the effect of diabetes on the functioning of nitric oxide system in the heart, lungs, liver and kidneys tissues of rats with traumatic brain injury (TBI). It has been shown that in TBI the general NO synthase activity and NOx content in the internal organs and blood serum of animals were significantly increased compared with control. The maximum changes of the studied parameters were observed in 24 hours after the injury. Concomitant diabetes mellitus leads to the even more pronounced increase in the NO synthase activity and NOx concentration. Rats with combined pathology showed the significantly higher studied parameters in comparison with the normoglycemic traumatized animals almost in all experimental periods (3 hours – 14 days). It has been concluded that the using of NO synthase modulators for the prevention of internal organs injuries could be effective in TBI on the diabetes background.
Keywords: traumatic cranial injury; diabetes mellitus; NO synthase; nitrites; nitrates